Using Facebook in Recruiting Kidney Transplant Recipients for a REDCap Study. (December 2019) - Chung, Shu-Yu; Hacker, Eileen D.; Rawl, Susan; Ellis, Rebecca; Bakas, Tamilyn; Jones, Josette; Welch, Janet
This web-based study recruited kidney transplant recipients from Facebook using three recruiting methods over a 5-week period. Participants completed 125 survey items via REDCap (Research Electronic Data Capture) survey. Facebook recruitment generated 153 eligible participants who completed surveys. The average survey response time was 15.07 min ( SD = 6.12; range: 4-43), with a low missing item rate (<5%). Facebook's standard ads were most effective for recruiting subjects ( n = 78, 51%), followed by three targeted Facebook kidney transplant support groups ( n = 52, 34%) and a pay-to-promote study page ( n = 12, 7.8%). The average cost paid for each valid survey was US2.19 through standard Facebook ads and US2.92 from the study page. The cost for online survey completion is economically feasible even for those with limited funds. Issues related to online surveys including extreme survey response times and participant misrepresentation were reported in this study.